Analysis of Ptkp Changes in the Pph 21 Calculation Scheme and Its Implications for Taxpayers - Akhmad Syarifudin (Jurnal Mantik, 2022)
Non-Taxable Income (PTKP) is a deduction factor in the income tax calculation scheme. In accordance with PMK No.0101/PMK/2016 PTKP increased and the final income tax rate according to PP 23/2018 decreased from 1% to 0.5%, while the corporate income tax rate remained the same. The purpose of the study was to determine the impact of changes in PTKP and its implications for PPh 21 payable for taxpayers. The study uses illustrative data of income level variations. The results of the study show that changes in PTKP have an impact on decreasing the amount of PPh 21 for WPOPs. Income of IDR 0.3 billion WPOP tax is lower than Corporate Income Tax, while income above IDR 0.6 billion WPOP tax increases to be higher than Corporate Income Tax. At the same income, corporate income tax with a turnover of up to IDR 50 billion is lower than the corporate income tax with a turnover of more than IDR 50 billion. Corporate taxpayers who do not receive tax facilities according to Article 31E of the Income Tax Law, have higher taxes than corporate taxpayers and corporate taxpayers who receive tax facilities so that it can lead to tax injustice. The final income tax calculation scheme for certain entrepreneurs based on turnover makes it easier, but burdensome for taxpayers if their business loses. These results can be input for tax subjects in planning taxation. The benefits for the government can be used as a review of policy considerations for adjustments in order to achieve a balance of tax rates for both WPOP, certain entrepreneurs, and corporate taxpayers. but burdensome WP if the business loses. These results can be input for tax subjects in planning taxation. The benefits for the government can be used as a review of policy considerations for adjustments in order to achieve a balance of tax rates for both WPOP, certain entrepreneurs, and corporate taxpayers. but burdensome WP if the business loses. These results can be input for tax subjects in planning taxation. The benefits for the government can be used as a review of policy considerations for adjustments in order to achieve a balance of tax rates for both WPOP, certain entrepreneurs, and corporate taxpayers